The Man in the Panther Skin - Shakespeare's Literary Source - Elguja Khintibidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The 12th century Georgian poet, Queen Tamar's eulogist Chakhrukhadze develops a messianic conception in his Thamariani: Thamar is a rescuer, messiah of the kingdom of the Georgians, the Georgian kingdom of Christianity and Christianity of mankind. Thamar is a rescuer, messiah. One stanza of the poem reads: "I said pale with fear. I take these words to mean the great responsibility with respect to the statement. My personal responsibility is enhanced by the fact that I, a Georgian researcher, intend to reveal and assert a hitherto absolutely unknown fact of Shakespeare, the peak of the world's literary thought, having looked into the national treasury of my nation. Will this not be taken by scholarly circles, primarily by foreign Shakespearian scholars, as a patriotic desire, excitement and overstatement? Following in the wake of my great teacher Korneli Kekelidze, I have always tried to be exempt from such charges in my scholarly activity. I recall the words of another outstanding Georgian Giorgi Merchule: Wise speech is pure silver, while silence is gold. Perhaps it is better to leave trouble alone the more so as silence costs so much? I think I have no right to leave trouble alone and fall silent in fear of what if regarding the views that have taken shape in my philological research of recent years and which I believe to be so important both for reading the unknown pages of the Georgian creative genius and for the interpretation of a highly significant issue of English literary criticism.